Dampak Kebijakan Anti-Monopoli terhadap Inovasi Startup Teknologi di Tengah Krisis Ekonomi Global 2025 - Anisa Rizki Aulia; Callista Putri Andani; Dinna Lorenza; M. Alfan Umirza Ag; Ridho Pratama; Ika Dwi Maya Roza (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
The rapid expansion of the digital economy has significantly accelerated the growth of technology startups while simultaneously increasing market concentration among dominant digital platforms. This condition has intensified the implementation of anti-monopoly policies as a regulatory instrument to maintain fair competition. Amid the ongoing global economic crisis extending into 2025, debates have emerged regarding whether anti-monopoly policies foster or hinder innovation among technology startups. This study aims to examine the impact of anti-monopoly policies on technology startup innovation within the context of the global economic crisis. The research adopts a qualitative approach using a narrative literature review and policy analysis. The data are derived from academic journal articles, scholarly books, and official reports issued by international organizations and competition authorities published within the last five years. The analysis is conducted through a descriptive-analytical method by synthesizing key findings related to anti-monopoly policy, technological innovation, digital market dynamics, and global economic conditions. The findings indicate that anti-monopoly policies can create a more equitable competitive environment for technology startups by limiting market dominance and abusive practices by large firms. However, during periods of global economic crisis, the effectiveness of such policies largely depends on regulatory design, consistency of enforcement, and the state’s capacity to balance competition protection with innovation incentives. Overly restrictive policies may suppress investment and startup growth, whereas adaptive and market-responsive regulations can enhance the resilience of technology startup innovation. This study contributes theoretical and policy insights for developing competition law frameworks that are more responsive to the challenges of the digital economy and global economic uncertainty.